DEKONSTRUKSI MAKNA “PRESTASI” PADA SISWA, GURU, DAN ORANG TUA SISWA - Luhjingga Panasari Urbaningrum; Nanang Martono; Elis Puspitasari; Agung Kurniawan (Jurnal Analisa Sosiologi, 2024)
This study aims to challenge the traditional concept of achievement often defined merely as formal recognition. It seeks a broader and more inclusive understanding of achievement by acknowledging various forms of success and abilities possessed by students. The research methodology employed is qualitative research. Data were collected through three main techniques: in-depth interviews, direct observation, and documentation. Informants for the study were purposively selected to ensure they possessed relevant knowledge and experience on the research topic, consisting of three students, two teachers, and three parents of students. Data obtained were analyzed using Interactive Analysis techniques. The findings of the study indicate that the definition of achievement extends beyond academic accomplishments to include personal development, social skills, and the ability to overcome challenges. The implications of this research are crucial in supporting every child to reach their full potential and in fostering an inclusive and supportive educational environment. Every child deserves recognition for their achievements, not only in academic fields but also in the development of personal skills and values that prepare them for the future, thereby promoting a more inclusive paradigm shift in the assessment and recognition of student achievements.